Islamic Education Institution Based on Islam Rahmatan Lil Alamin: The Contribution of Kh. A. Hasyim Muzadi in Realizing Religion Peace and Harmony - Mutholingah, Siti (Proceedings of Annual Conference for Muslim Scholars, 2022)
KH. A. Hasyim Muzadi is one of Indonesia's Muslim scholars who is known as a very moderate figure and active in efforts to realize religion peace and harmony not only in Indonesia, but also in the international community. Furthermore, KH. A. Hasyim Muzadi also founded the pesantren mahasiswa al-Hikam Malang as one of the efforts in realizing religious harmony, and this pesantren is the object of this research. The aim of this study is to find out the contribution of pesantren mahasiswa al-Hikam Malang in realizing religious peace and harmony. This study uses a qualitative approach with a type of case study research. The results of this study are the contribution of Pesantren Mahasiswa al-Hikam Malang in realizing religious peace and harmony namely realizing Islamic education process based on Islam rahmatan lil’alamin and establishing inclusive students.